Chosen? : reading the Bible amid the Israeli-Palestinian conflict - Brueggemann, Walter (Louisville, KY : Westminster John Knox Press, 2015)
"The conflict is only 'seemingly' beyond solution, because all historical-political problems have solutions, if there is enough courage, honesty, and steadfastness." n Chosen?, Walter Brueggemann explores the situation in modern-day Israel that raises questions for many Christians who are easily confused when reading biblical accounts of God's saving actions with the Israelites. Are modern Israeli citizens the descendants of the Israelites in the Bible whom God called chosen? Was the promise of land to Moses permanent and irrevocable? What about others living in the promised land? How should we read the Bible in light of the modern situation? Who are the Zionists, and what do they say? In four chapters, Brueggemann addresses the main questions people have with regards to what the Bible has to say about this ongoing issue. A question-and-answer section with Walter Brueggemann, a glossary of terms, study guide, and guidelines for respectful dialogue are also included. The reader will get answers to their key questions about how to understand God's promises to the biblical people often called Israel and the conflict between Israel and Palestine today.
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Textbooks; Arab-Israeli conflict -- Religious aspects -- Christianity